2017
DOI: 10.1155/2017/3130723
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Induced Bleaching in the Sea Anemone Exaiptasia Supports Glucose as a Main Metabolite Associated with Its Symbiosis

Abstract: Our current understanding of carbon exchange between partners in the Symbiodinium-cnidarian symbioses is still limited, even though studies employing carbon isotopes have made us aware of the metabolic complexity of this exchange. We examined glycerol and glucose metabolism to better understand how photosynthates are exchanged between host and symbiont. The levels of these metabolites were compared between symbiotic and bleached Exaiptasia pallida anemones, assaying enzymes directly involved in their metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the loss of endosymbionts following a bleaching event results in the loss of essential nutrient provision (e.g., carbon and nitrogen [36]). During this time, anemones underwent a negative growth period, similar to what has been found during times of high stress or starvation [30,37], by consuming their own fatty acid reserves [38]. This mechanism of negative growth is likely responsible for enabling the maintenance of anemone toxicity and ultimately survival until the acquisition of new symbiotic algae.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, the loss of endosymbionts following a bleaching event results in the loss of essential nutrient provision (e.g., carbon and nitrogen [36]). During this time, anemones underwent a negative growth period, similar to what has been found during times of high stress or starvation [30,37], by consuming their own fatty acid reserves [38]. This mechanism of negative growth is likely responsible for enabling the maintenance of anemone toxicity and ultimately survival until the acquisition of new symbiotic algae.…”
Section: Discussionmentioning
confidence: 74%
“…In this context, identifying the chemical form of photosynthates or so-called "mobile compounds" (Trench, 1971;Venn et al, 2008) has proven challenging, although it most likely involves complex metabolic modifications. In other well-known examples of algal-cnidarian symbiotic relationships in scleractinian corals, glycerol is the dominant photosynthate produced (Gattuso et al, 1993;Hagedorn et al, 2010), while glucose is the dominant photosynthate in the sea anemone genus Exaiptasia (formerly Aiptasia) (Burriesci et al, 2012;Molina et al, 2017). Early 14 C (radiocarbon) labeling studies in C. andromeda showed that glucose and glycerol were the only two free metabolites detected after short term labeling (3-60 min) in medusa tissue for samples incubated in the light (Hofmann and Kremer, 1981).…”
Section: Nutritional Requirementsmentioning
confidence: 99%
“…This study aims to examine (1) whether E. diaphana from the GBR, which harbours B. minutum as its homologous symbiont, can form a stable symbiosis with heterologous wild-type and heat-evolved Cladocopium C1 acro , and (2) the nutritional consequences of the respective Cladocopium C1 acro associations with specific focus on central carbon metabolism. Since glucose is a key form in which Symbiodiniaceae translocate fixed carbon to the cnidarian host [ 2 , 30 ], particular focus is given to sugar-related metabolites.…”
Section: Introductionmentioning
confidence: 99%